EFL SUCCESSFUL LEARNERS’ PERCEPTION ON THE USE OF COGNITIVE STRATEGIES IN SPEAKING PERFORMANCE - Tahmina, Tania (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
EFL learners adopt various strategies to speak effectively. Cognitive learning strategies assist them to speak easily and comfortably. The aim of this research was to explore the most frequently used cognitive strategies which were employed by the successful learners of the Department of English, Jagannath University, Dhaka, Bangladesh, in their speaking class. In this study, a mixed-methods approach was used to collect the data. The subjects of this research were eighteen (six males and nine females) successful learners. Oxford’s (1990) SILL (“Strategy Inventory for Language Learning”) questionnaire was employed to collect the data. The interview provided answers to the questions, which was helpful to comprehend the learners’ perceptions better and to validate the quantitative data. The completed questionnaires were collected and analyzed descriptively. The result showed that the most frequently used cognitive strategy which the successful learners employed to develop their speaking skills was “I say or write new English words several times” (60%). The next most frequently used strategy was a cognitive strategy “I watch English language TV shows spoken in English or go to movies spoken in English” (46.66%). This was followed by the cognitive strategies “I practice the sounds of English” (40%) and “I find the meaning of an English word by dividing it into parts that I understand” (40%). The data will assist learners, teachers and researchers for the improvement of future teaching-learning processes.